Aktivitas Menggigit Nyamuk Culex quinquefasciatus Di Daerah Endemis Filariasis Limfatik Kelurahan Pabean Kota Pekalongan Provinsi Jawa Tengah - Tri Ramadhani (Loka Litbang Kesehatan Pangandaran, 2009)
Abstract. Pabean villages is a filariasis endemic areas caused by Whuchereria bancrofti parasite with incidence rate is 3.4% on year 2007. To determine biting activity of Culex quinquefasciatus mosquitoes that been confirmed as filariasis’s vector, it been conducted a entomological survey as long as 5 months (from August up to December) every 2 weeks that aimed to know mosquito’s peak biting and resting density in each hour catching. A survey was conducted using all night landing collection method from 18.00 am up to 06.00 pm. In each hour survey; indoor and outdoor landing mosquitoes and also resting mosquitoes on inside wall and cattle stable, will be caught using aspirator and put onto paper cup.A study result was showed that indoor peak of Cx. quinquefasciatus mosquitoes biting densi-ty is 20.00, 22.00 and 23.00 o’clock, whereas the outside peak one is 21.00, 24.00 and 02.00 o’clock; peak of resting on inside wall is 18.00 o’clock and cattle stable resting is 24.00 o’clock.